2023
DOI: 10.1007/s12035-022-03201-x
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Sulforaphane on Oxidative Stress and Mitochondrial Dysfunction Associated with Status Epilepticus in Immature Rats

Abstract: The present study aimed to elucidate the effect of sulforaphane (a natural isothiocyanate) on oxidative stress and mitochondrial dysfunction during and at selected periods following status epilepticus (SE) induced in immature 12-day-old rats by Li-pilocarpine. Dihydroethidium was employed for the detection of superoxide anions, immunoblot analyses for 3-nitrotyrosine (3-NT) and 4-hydroxynonenal (4-HNE) levels and respiratory chain complex I activity for evaluation of mitochondrial function. Sulforaphane was gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 97 publications
(134 reference statements)
0
4
0
Order By: Relevance
“…Dietary supplementation with dried broccoli sprouts (BrSp, a good source of SFN) (300 mg/kg) ameliorated hypertension and improved glucose tolerance in male Long-Evans rats and suppressed visceral fat accumulation in female rats [40]. Pretreatment with SFN (5 mg/kg) significantly reduced the expression of oxidative stress and mitochondrial dysfunction markers in 12-day-old male Wistar rats [41]. Intraperitoneal injection of SFN (10 mg/kg) for 30 days reduced HFD-induced body weight gain in female mice [42].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary supplementation with dried broccoli sprouts (BrSp, a good source of SFN) (300 mg/kg) ameliorated hypertension and improved glucose tolerance in male Long-Evans rats and suppressed visceral fat accumulation in female rats [40]. Pretreatment with SFN (5 mg/kg) significantly reduced the expression of oxidative stress and mitochondrial dysfunction markers in 12-day-old male Wistar rats [41]. Intraperitoneal injection of SFN (10 mg/kg) for 30 days reduced HFD-induced body weight gain in female mice [42].…”
Section: Discussionmentioning
confidence: 99%
“…As an agonist of Nrf2, SFN in uences antioxidation-related molecular processes. SFN has high antioxidant capacity and the ability to inhibit superoxide anion O -2 [34]. It can activate Nrf2, leading to the upregulation of antioxidant proteins, such as HO-1, SOD, and glutathione s-transferase [34].…”
Section: Discussionmentioning
confidence: 99%
“…SFN has high antioxidant capacity and the ability to inhibit superoxide anion O -2 [34]. It can activate Nrf2, leading to the upregulation of antioxidant proteins, such as HO-1, SOD, and glutathione s-transferase [34]. Kubo et al [35] found that during the aging process of lens epithelial cells, the binding of the promoter of peroxiredoxin 6 (Prdx6) to the Nrf2/ARE regulatory region (357/349) gradually decreased, leading to the generation of oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…However, they could not demonstrate a particular effect on the development of convulsions. [20][21][22] Studies that reported the beneficial effects of the administration of antioxidants, such as NAC and sulforaphane (SFN), have also been carried out. 23,24 Moreover, PTZ triggers various toxic conditions by possibly supporting oxidation that causes seizures.…”
Section: Discussionmentioning
confidence: 99%